Demography factors and students’ academic performance in secondary schools - Imran, M.; Afshari, M.; Ghavifekr, S.; Razak, Ahmad Zabidi Abdul (Department of Educational Management, Planning & Policy, Faculty of Education, University of Malaya, 2013)
Many researchers believe that academic performance is one of the important predictors of success of an educational system. Students’ academic performance can also be considered as a point of comparison among educational institutions with the focus of success at both national and global level. The aim of this study was to investigate the relationship between demographic factors and academic performance in the secondary schools in Maldives. Findings of this study indicated that there was a significant association between age and academic performance. At the same time, it reported a significant association between socioeconomic status and academic performance. However, the researcher found no evidence to support the existing a significant association between gender and academic performance. These results support previous research and possible directions for public policy are given.